Peningkatan Hasil Belajar Bahasa Indonesia Kelas 3 SD Negeri 1 Ngroto dengan Menggunakan Model Pembelajaran Numbered Heads Together (NHT) - Nur Aziroh (Action Research Journal, 2022)
The aim of this research is to improve the learning outcomes of grade 3 students at SD Negeri 1 Ngroto, Gubug District, Grobogan Regency using the Numbered Heads Together (NHT) Learning Model for the Odd 2021/2022 academic year. The method in this research is the classroom action research method by applying cycle I and cycle II. The data collection technique in this research is documentation technique, written tests through cycle I and cycle II. Data analysis in this research is student learning outcomes in cycle I and student learning outcomes in cycle II using descriptive statistical tests. Students are said to obtain maximum results if the student's test score is more than the KKM, namely 75. The success indicator used is successful if it increases by more than or equal to 85% of the total number of 3rd grade elementary school students who reach the KKM, namely 75. The results of this research are an increase student learning outcomes from cycle I to cycle II and achieving classical learning completeness in cycle II.